Sustainable Vermicomposter Design for Household Usage - Mohd Sani, Nor Aqilah; Awang, Zarizi (Progress in Engineering Application and Technology, 2021)
Mostly, the food waste that is produced will be disposed of in landfills. Therefore, by applying the concept of food waste recycling, it may be an interesting option for reducing landfill use. In this study, vermicomposting is an alternative method for food waste recycling since it is eco-friendly and cost-effective. In the vermicomposting process, the red worm (Eisenia fetida) is used for the decomposition of food waste. The food waste was collected from the household and segregated into two categories which are food waste that is suitable and unsuitable for the worm. The amount of food waste that worms can consume from the household is known and the data was used for the efficiency of the vermicomposting bin. The 3-tier plastic drawer is used as a vermicomposting bin. The maximum volume of food waste that fitter on first and second drawer including the bedding materials was 8.988kg. Ready-made vermicompost will be used on Brazilian spinach plants with four different treatments, T1, T2, T3, and T4 to access the ability of vermicompost as an organic fertilizer for plant growth. From several parameters, T3 shows an improvement of the plant growth compared to other treatments.